Parliament and the War Prerogative in the United Kingdom and Canada: Explaining Variations in Institutional Change and Legislative Control. Issue 2 (13th September 2016) - Lagassé, Philippe
Abstract : The British and Canadian Parliaments have no legal control over military deployment decisions. Recently, however, governments in both countries have held votes in the House of Commons on expeditionary missions involving combat. In the United Kingdom, this has led to a convention of legislative control of the executive's prerogative to deploy the armed forces. In Canada, the votes have benefited and enabled the executive, rather than strengthening legislative control. Using Mahoney and Thelen's (2010) theory of gradual institutional change, this article analyses how and why war prerogative reforms in the United Kingdom and Canada have resulted in different outcomes.